The use of biomass as a factor for increasing the energy-ecological efficiency of boiler plants and ensuring energy sustainability in conditions of martial law - Pravoverov, A.; Romanova, K. (Energy and Automation, 2026)
The disruption of energy infrastructure functioning in Ukraine under martial law exacerbates the problem of ensuring reliable heat supply. The dependence of boiler plants on natural gas reduces their resilience to crisis impacts, highlighting the need to transition to alternative and locally available energy sources, particularly biomass.The aim of this article is to assess the potential of using biomass to enhance the energy and environmental efficiency of boiler plants and ensure their energy resilience. To achieve this goal, the study focuses on identifying key characteristics of biofuels, evaluating their impact on boiler performance, and substantiating the feasibility of implementing bioenergy solutions based on international experience.The study employs a comparative analysis of the characteristics of natural gas and various types of biomasses, a systems approach to considering boiler plants as integrated energy-technological systems, calculation methods for assessing thermal and economic performance indicators, as well as elements of experimental analysis of fuel composition and generalization of foreign experience.It has been established that using biomass contributes to increasing the energy autonomy of boiler plants and reducing the cost of heat production compared to natural gas. The efficiency of biofuel boiler operations depends on the consistency of their technological components and the consideration of fuel properties. The feasibility of using wood pellets and torrefied biomass for medium-capacity boiler plants is substantiated, while agro-biomass requires accounting for corrosion and slagging risks. The adaptation of European bioenergy models to domestic conditions is demonstrated.The use of biomass is an effective approach to improving the energy-environmental efficiency and resilience of heat supply systems under martial law. Transitioning to biofuels ensures diversification of energy sources, reduces dependence on imported resources, and promotes the development of local fuel markets. Implementing this approach requires a comprehensive consideration of technical, economic, and resource factors.Recieved 2025-11-21Recieved 2026-01-21Accepted 2026-02-11
Keywords: biomass; boiler plants; energy resilience; martial law; renewable energy; biofuel; energy independence; systemic outages; heat supply